Analisis Peraturan Pemerintah Nomor 23 Tahun 2018: Sudut Pandang Pelaku UMKM - Prima Bayu Prakosa; Amir Hidayatulloh (Jurnal Akuntansi dan Pajak, 2019)
This research was conducted to determine the effectiveness of final tax enforcement for MSME entrepreneurs in terms of tax collection principles and to find out the obstacles faxed by MSME entrepreneurs in implementing the final tax. This research is a qualitative study. The analysis of the determination of final income tax base on government regulation number 23 in 2018 provides an explanation of the phenomenon of imposing final tax on MSME. Data collection techniques used were interviews, which given to nine Batik MSME in the special regional of Yogyakarta. The next activity is analyzing by linking the real conditions with particular review that used as a review that is used as reference and guide in conducting a study. Base on the analysis, it was found that the majority of taxpayer (nine batik MSME) said that MSME left injustice, lack of legal certainty, lack of efficiency, and lack of pleasure in paying taxes. Obstacles in implementing government regulation number 23 in 2018 include the existence of government policies related to taxation when in a state of loss makes MSME difficult, the payment system that e-billing makes it is difficult for some MSME because the resource person does not master the internet and computerization, legal certainly is unclear and the existence of problem related to financial statements that have not been properly arranged.